Implementation of kansei engineering in the design of packaging design elements: study case for Food MSME - Sari, Novi Purnama; Rahmadianto, Muhammad Athariq; Ramadhan, Raihan Thoriq; Napitupulu, Yesaya Firdaus (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
The current packaging of Rangi Cake products in the market is criticized for its simplicity and lack of adequate safety features, which compromises both product safety and visual appeal. To address this, a research initiative was undertaken to enhance the design and functionality of Rangi Cake packaging. The study employed Kansei engineering to discern consumer preferences regarding packaging. The findings incorporated 46 packaging samples and identified 44 Kansei words. Utilizing Principal Component Analysis (PCA), two design concepts emerged: "Standard-simple" and "informative-efficient." The "standard-simple" concept, with the highest R-Square value of 0.9615 through QTT-1 results, was selected for further development. The design elements derived from consumer preferences include a square shape, kraft cardboard material, window feature, typography design, minimalist style, surface sticker, gray color, and header card/topper cover shape. The packaging design, based on these elements, was translated into 3D mockups. Survey results indicated a preference for the Reusable concept mockup (PC2). Sample evaluation, conducted using fuzzy logic on the PC1 sample, yielded a value of 4.0, affirming the positive reception of the redesigned packaging concept. This research contributes to elevating the visual appeal and functionality of Rangi Cake packaging, aligning it more closely with consumer preferences.